PEWARTAAN IMAN DAN BUDAYA: SENI MUSIK GEJOG LESUNG SEBAGAI MEDIA PEWARTAAN IMAN - Antonius Virdei Eresto Gaudiawan; Maria Reni Widi Astuti (Lembaga Penelitian STKIP Widya Yuwana, 2026)
This study aims to examine the extent to which gejog lesung music can be utilized as a medium for faith proclamation (evangelization). Gejog lesung is a cultural heritage originating from agricultural communities, where the lesung (a traditional wooden mortar) was historically used for pounding rice. During intervals of their work, the lesung was played as klothekan (rhythmic percussion) to accompany songs that entertained those resting from their labor. In St. Hilarius Parish, Klepu, Ponorogo, gejog lesung has been revitalized and developed as part of the local agricultural culture, eventually becoming a distinctive icon of the parish. This research employed a qualitative approach using semi-structured and in-depth interviews. The study was conducted at St. Hilarius Parish, Klepu, Ponorogo, due to its deep-rooted agricultural culture and the preservation of the gejog lesung tradition. The community has successfully revived this nearly lost art form and integrated it as a signature identity of the parish. The findings highlight several key points. First, the Catholic Church has the duty and responsibility to preserve, maintain, and purify local cultures such as gejog lesung, ensuring they do not vanish but instead flourish while being enriched with Christian values. St. Hilarius Parish serves as a model for the Church in revitalizing local traditions. Second, gejog lesung demonstrates that simple folk art can serve as an effective medium for faith proclamation. However, guidance from parish priests or theologians is essential to transform gejog lesung into a form of catechesis that conveys ecclesiastical reflections. Artistic language as a catechetical tool proves to be more engaging and accessible for laypeople. Third, gejog lesung fosters communal participation in the mission of the Church. Since this art form cannot be performed individually, it necessitates cooperation and collaboration among the faithful in their evangelical work.